Introduction [in Agriculture on the road to industrialization] - Mellor, John W. (International Food Policy Research Institute, 1995)
"The faster agriculture grows, the faster its relative size declines." That quotation from The Economics of Agricultural Development (Mellor 1966) still captures the essence of agricultural growth and its causal relationship to the structural transformation and aggregate growth of an economy.